Revisiting the informal aspects of the activity of countries, studied through Social Accounting and Socio-Demographic Matrices, with an application to Mozambique - Santos, Susana (2021)
Approaches based on Social Accounting Matrices (SAMs) and Socio-Demographic Matrices (SDMs) will be presented as a way of capturing relevant networks of linkages and the corresponding multiplier effects, which can subsequently be used for modelling the activity of the countries to be studied. Emphasis will be placed on the activity of household unincorporated enterprises that will be identified with the informal sector. Based on methodological principles derived mainly from the works of Richard Stone, a proposal will be made to study the economic activity of Mozambique in 2016 in a matrix format, with special attention to the informal sector in general and, within this, forestry, and logging. Such a proposal includes, on the one hand, people – represented by a SDM – and, on the other hand, activities, products, factors of production and institutions – represented by a SAM. The exposition will mostly be accompanied by an application to the above-mentioned reality. Scenarios, involving changes in functional and institutional distribution of income, will be presented and the macroeconomic effects of these changes, will be summarised in the form of changes in the macroeconomic aggregates, such as, Gross Domestic Product, Gross National Income and Disposable Income.